Molecular cloning and characterisation of the 5’-untranslated region and promoters in human peroxisome proliferator-activated receptor alpha (hPPARα) - Chew , and , Choy Hoong; Najimudin, Nazalan; Muhammad, Tengku Sifzizul Tengku (Penerbit Universiti Sains Malaysia, 2004)
The peroxisome proliferator activated receptors (PPARs) are members of the nuclear hormone receptor gene superfamily of ligandactivated transcription factors [Issemann and Green, 1990].